Establishment of occupation chronicles in Grotte Mandrin using sooted concretions: Rethinking the Middle to Upper Paleolithic transition. Issue 112 (November 2017) - Vandevelde, Ségolène; Brochier, Jacques Élie; Petit, Christophe; Slimak, Ludovic
Abstract: Soot marks, witnesses of past human activities, can sometimes be noticed in concretions (speleothem, travertine, carbonated crust, etc.) formed in cavities. We demonstrate here that these deposits, generally ignored in archaeological studies, turned out to be a perfectly suitable material for micro-chronological study of hominin activities in a site. At the Grotte Mandrin (Mediterranean France), thousands of clastic fragments from the rock walls were found in every archaeological level of the shelter. Calcareous crusts containing soot deposits are recorded on some of their surfaces. They appear in thin section as thin black laminae. Microscopic observation of these crusts revealed that they kept track of many occupations. We show that is possible to link them with the archaeological units identified during the excavation. Minimum Number of Occupations (MNO) can be built out of these sooted crusts. MNO are usually high and attest to the cumulative nature of each archaeological unit. They are witnesses of each occupation of hominin groups in each archaeological level of the cave. This study also shows that, in Grotte Mandrin, a very short time separates the first Middle/Upper Paleolithic transitional groups' occupations from those of the last Mousterians. The research perspectives on soot deposits are diversified and raise the possibility of studying multiple aspects of past human life, and in this case, to rethink the Middle/Upper Paleolithic transition, with an unmatched temporal resolution. Sooted concretion analysis provides high temporal resolution archaeology. There is a real possibility of extending this study with chronological implications to cavities of all ages and areas.